2015
DOI: 10.1186/s12865-015-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioid inhibition of proliferation of T and B cell subpopulations in response to immunization for experimental autoimmune encephalomyelitis

Abstract: BackgroundExperimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis, is induced by immunization of mice with myelin oligodendrocytic glycoprotein (MOG35-55) injections, and after 9 days, mice develop behavioral signs of chronic progressive EAE. Proliferation of T and B cells located in peripheral lymph tissues such as spleen and inguinal lymph nodes of C57BL/6J mice are stimulated. The opioid growth factor-opioid growth factor receptor (OGF-OGFr) axis has been shown to effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
(54 reference statements)
3
29
0
2
Order By: Relevance
“…Animal studies using both models of EAE confirmed our findings that OGF, exogenously or endogenously stimulated following LDN, inhibited T-cell and (35,36). Examination of peripheral lymphocyte dynamics following immunization of mice with MOG antigen and treatment with OGF or LDN was conducted over a 2-week period following immunization (35,36). Isolated lymphocytes from spleens and draining inguinal lymph nodes were counted by flow cytometry, and the subpopulations of CD4+ and CD8+ T-cells, as well as B-lymphocytes, were noted.…”
Section: Ogf Reduction Of T-lymphocytes and B-lymphocytessupporting
confidence: 84%
See 3 more Smart Citations
“…Animal studies using both models of EAE confirmed our findings that OGF, exogenously or endogenously stimulated following LDN, inhibited T-cell and (35,36). Examination of peripheral lymphocyte dynamics following immunization of mice with MOG antigen and treatment with OGF or LDN was conducted over a 2-week period following immunization (35,36). Isolated lymphocytes from spleens and draining inguinal lymph nodes were counted by flow cytometry, and the subpopulations of CD4+ and CD8+ T-cells, as well as B-lymphocytes, were noted.…”
Section: Ogf Reduction Of T-lymphocytes and B-lymphocytessupporting
confidence: 84%
“…While this model falls short of mimicking clinical reality, the studies revealed that direct application of OGF or LDN to activated splenocytes inhibited T-cell and B-cell proliferation without requiring intervention from other immune system mediators. Animal studies using both models of EAE confirmed our findings that OGF, exogenously or endogenously stimulated following LDN, inhibited T-cell and (35,36). Examination of peripheral lymphocyte dynamics following immunization of mice with MOG antigen and treatment with OGF or LDN was conducted over a 2-week period following immunization (35,36).…”
Section: Ogf Reduction Of T-lymphocytes and B-lymphocytessupporting
confidence: 74%
See 2 more Smart Citations
“…15 The OGF-OGFr axis is a key regulatory pathway in maintaining homeostasis of immune cell replication. [17][18][19] Modulation of the OGF-OGFr axis is effective in the treatment of experimental autoimmune encephalomyelitis (EAE), the accepted mouse model of MS. In both the chronic (Ch-EAE) and relapsing remitting (RR-EAE) models, treatment with either exogenous OGF or upregulation of endogenous enkephalins with LDN, effectively reduced the overall disease severity of EAE and diminished associated neuropathology.…”
Section: Introductionmentioning
confidence: 99%